Ischaemic stroke complicating primary percutaneous coronary intervention in patients with ST elevation myocardial infarction - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
Objective - We sought to determine the in-hospital incidence and predictors of ischaemic stroke in patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods - We reviewed 2638 consecutive patients undergoing 2722 pimary PCI procedures for STEMI during in-hospital stay. Stroke was defined as any new focal neurological deficit lasting >= 24 h, occurring anytime during or after PCI until discharge. Patients with haemorrhagic stroke were excluded. Clinical characteristics and in-hospital outcome were analysed regarding ischaemic stroke in patients undergoing primary PCI. Results - Ischaemic stroke was observed in 20 of the 2722 procedures, an incidence of 0.73%. Patients with ischaemic stroke were older than patients without stroke (mean age 67 +/- 9.6 vs. 56.6 +/- 11.8, P < 0.001). Compared to patients without stroke, female gender, diabetes and hypertension were more prevalent in patients with stroke. Ischaemic stroke was found to be a powerful independent predictor of in-hospital cardiovascular mortality (odds ratio [OR] 6.32, 1.15-34.7; P < 0.001). Left ventricular ejection fraction (LVEF) < 35% (OR 3.13, P = 0.04), contrast-induced nephropathy (OR 2.91, P = 0.04) and tirofiban use (OR 0.23, P = 0.02) were the independent predictors for in-hospital ischaemic stroke. Conclusions - The present Study shows that the incidence of ischaemic stroke in patients undergoing PCI for STEMI is higher and ischaemic stroke increases in-hospital mortality in these patients. Moreover, LVEF < 35% and contrast-induced nephropathy were independent predictors of ischaemic stroke, whereas tirofiban use demonstrated a protective effect to this potentially catastrophic complication.
Keywords: ST elevation myocardial infarction; primary percutaneous coronary intervention; ischaemic stroke; prognosis; primary angioplasty; tirofiban; mortality; CLINICAL FINDINGS; GLOBAL REGISTRY; RISK-FACTORS; THROMBOLYSIS; ANGIOPLASTY; MORTALITY; OUTCOMES; EVENTS; REVASCULARIZATION; MANAGEMENT